Knowledge of responsible technical nurses on management skills: a qualitative study - Cibele Leite Siqueira; Andrea Cristiane Ferreira Bernadeli; Renata Cristina Gasparino; Liliane Bauer Feldman; Isabel Cristina Kowal Olm Cunha; Ramon Antônio Oliveira
ABSTRACT Objective: To identify the knowledge of responsible technical nurses in relation to the general and management skills required to perform this function. Method: Qualitative case study with 14 nurses. The semi-structured interviews were recorded and the data analyzed through the thematic content analysis. Results: Two categories stood out: Main Responsibilities for the Position of Technical Manager: Leadership, Interpersonal Relationship and Systemic view; and Developing Skills: Dissociation between Theory and Practice. Final considerations: The fact that only three skills have been recognized as necessary for the exercise of the function of technical leader and the perception of the interviewees about the dissociation between theory and practice during graduation should be explored by the teaching and health institutions, because to exercise this nurses must develop the technical-scientific, socio-educational and ethical-political skills to be able to lead the organization to positive results..